Internationalization processes and links with capital factors: the case of South Africa - Urban, Boris; Shree, Sanam (Business: Theory and Practice, 2012)
Several different theoretical perspectives were examined in terms of the internationalisation processes of entrepreneurial firms. This article is built on past studies that recognize the case that when an entrepreneurial firm undertakes an internationalization strategy, financial, social and human capital factors all play a major role in its success or failure. Based on a survey of 136 internationalized and non-internationalized firms the study conducts a comparative analysis of capital factors that may act as inhibitors or promoters of internationalization. Descriptive and multivariate statistical analyses were used to analyse various features of internationalization and perception of capital factors. Results confirm that financial capital items are perceived as inhibitors to the firm’s ability to internationalize in the emerging market context. Findings provide organisations and practitioners with additional insights into the key capital constraints on internationalization of entrepreneurial firms.